Odgovornost direktorjev in nadzornikov za družbeno odgovorno poslovanje podjetja - Bratina, Borut (Podjetje in delo, 2023)
In this article, the author discusses the issue of the transition of corporate governance from profit-making to sustainable business operations, with a view to reducing the adverse impact on the natural environment. In the second chapter, the author attempts to more precisely define the concept of "socially responsible business". In doing so, the author distinguishes between the concept of sustainability from the concept of sustainable development. Directors must manage the company with the diligence of a conscientious and honest businessman, taking into account the interests of company. The author asks when a caring and responsible attitude towards nature will become a legitimate corporate objective, alongside profit-making. In a separate chapter, the author analyses the significance and impact that the EU Directive on due diligence in business will have on sustainability. In doing so, the author concludes that the introduction of criminal and civil liability for companies and their directors and supervisors for company (un)sustainable corporate behaviour must be done at a global level, as otherwise companies will relocate their headquarters to countries with a lower level of protection of the natural environment.
Keywords: antropocentrizem; družbena odgovornost; gospodarske družbe; odškodninska odgovornost; Trajnostni razvoj; trajnostnost